Adult resistance genes to barley powdery mildew confer basal penetration resistance associated with broad-spectrum resistance - Ge, Cynthia; Wentzel, Elzette; D'Souza, Nola; Chen, Kefei; Oliver, Richard; Ellwood, Simon (2021)
Powdery mildew isa major disease of barley (Hordeum vulgare L.) for which breeders have traditionally relied on dominant, pathogen race-specific resistance genes for genetic control. Directional selection pressures in extensive monocultures invariably result in such genes being overcome as the pathogen mutates to evade recognition. This has led to a widespread reliance on fungicides and a single broad-spectrum recessive resistance provided by the mlo gene. The range of resistance genes and alleles found in wild crop relatives and landraces has been reduced in agricultural cultivars through an erosion of genetic diversity during domestication and selective breeding. Three novel major-effect adult plant resistance (APR) genes from landraces, designated Resistance to Blumeria graminis f. sp. hordei (Rbgh1 to Rbgh3), were identified in the terminal regions of barley chromosomes 5HL, 7HS, and 1HS, respectively. The phenotype of the new APR genes showed neither pronounced penetration resistance, nor the spontaneous necrosis and mesophyll cell death typical of mlo resistance, nor a whole epidermal cell hypersensitive response, typical of race-specific resistance. Instead, resistance was localized to the site of attempted penetration in an epidermal cell and was associated with cell wall appositions and cytosolic vesicle-like bodies, and lacked strong induction of reactive oxygen species. The APR genes exhibited differences in vesicle-like body sizes, their distribution, and the extent of localized 3,3-diaminobenzidine staining in individual doubled haploid lines. The results revealed a set of unique basal penetration resistance genes that offer opportunities for combining different resistance mechanisms in breeding programs for robust mildew resistance.